Chlorination of Arylaldehyde-Derived Arylsulfonylhydrazones with N-Chlorosuccinimide Leading to 1,2,4,5-Tetrazine Derivatives - Ji, Yuan-Zhao; Li, Hui-Jing; Liu, Ying; Wu, Yan-Chao (Synthesis, 2020)
It has been reported previously that treatment of arylketone-derived arylsulfonylhydrazones with NXS/(nBu)4NX affords exclusively vinyl halides. In contrast, we have found that treatment of arylaldehyde-derived arylsulfonylhydrazones with N-chlorosuccinimide in the presence of potassium hydroxide affords 1,2,4,5-tetrazine derivatives in good to excellent yields. The present reactions are carried out under metal-free and mild reaction conditions.
Keywords: 1,2,4,5-tetrazines; hydrazones; N-chlorosuccinimide; chlorination; metal-free